Ultrasonic-assisted synthesis, characterization, and optical properties of Sb doped ZnO and their photocatalytic activities - Anukorn Phuruangrat (2018)
Sb doped ZnO nanostructures were synthesized by an ultrasonic-assisted method. Effect of Sb dopant on the structure, morphology, and composition of as-synthesized Sb doped ZnO nanostructures was investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, and transmission electron microscopy (TEM). All samples were identified to wurtzite hexagonal ZnO structure. UV-visible spectra of the as-synthesized 3% Sb doped ZnO sample exhibit broad absorption bands at around 343 nm which is blue shift of 373 nm of pure ZnO. The photocatalytic activity was tested by decolorization of methylene blue (MB) solution under UV light. After 300 min irradiation, the degradation efficiencies were 56, 90, and 95% for ZnO, 1% Sb doped ZnO, and 3% Sb doped ZnO, respectively. The 3% Sb doped ZnO shows the highest photocatalytic activity than any other samples. © 2014 Anukorn Phuruangrat et al.